Kemuliaan Wanita Dibalik Narasi Superioritas Maskulin Dalam Al-Qur’an : (Telaah Pemikiran 'Abbas Mahmud al-‘Aqqad Dalam Kitab Al-Mar'ah Fi al-Qur'an) - Basri; Podungge, Mariaty; Misbahuddin Asaad (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2024)
This study aims to critically describe the glory of women behind the narrative of masculine superiority in the Qur’an. The material object of this research is the result of ‘Abbas Mahmud al-‘Aqqad’s interpretation in the book al-Mar’ah fi al-Qur’an. Broadly speaking, the book outlines the solution to the problems faced by women in the laws contained in the Qur’an. This type of research is library research. Using qualitative methods, the author collects data from various literature. Data sources include two types, namely primary sources and secondary sources. The primary source of data is the book al-Mar’ah fi al-Qur’an by ‘Abbas Mahmud al-‘Aqqad. Secondary data sources, namely various kinds of literature from books and journals related to the object of discussion. The results of the study show that by using the interpretation model of the maudhu’i (thematic) method, al-‘Aqqad explains the problem of the superiority of men over women based on three interrelated verses. Namely: QS al-Baqarah/2: 228, QS al-Nisa’/4: 32, and QS al-Nisa’/4: 34. He then analyzed the verse by facing it with the reality that occurred in the midst of society as evidence of the concept he carried out in order to create the benefit of mankind. For al-‘Aqqad, the narrative of the verses of the Qur’an that hint at the superiority of men over women contains the wisdom that it is a gesture to glorify the woman herself.